How to analyse the performances of innovative variable diffusivity membranes integrated within prefabricated timber facades Compute - Riccardo Pinotti; Stefano Avesani; Francesco Babich; Andrea Gasparella; Alice Speranza (Journal of Facade Design and Engineering, 2018)
Vapour barriers and retarders are often needed to improve the hygro-thermal performance of the building envelope. Their use is particularly important in prefabricated timber façades, especially when critical boundary conditions occur. In the literature, very little is known about the actual performance of complete envelope packages that integrate these membranes, since most previous studies focused on the analysis of single components. However, considering the growing interest and use of such timber facade elements, an analysis of the performance of integrated membranes is needed in order to improve the material function curves available in the datasheets to enable the correct design of the whole wall structure. Thus, the novelty of this work lies in the validated analysis of a building envelope sample that integrates membranes with a variable vapour diffusivity.